ATP-Dependent Binding Cassette Transporter G Family Member 16 Increases Plant Tolerance to Abscisic Acid and Assists in Basal Resistance against Pseudomonas syringae DC3000 . Issue 2 (21st August 2014) - Ji, Hao; Peng, Yanhui; Meckes, Nicole; Allen, Sara; Stewart, C. Neal; Traw, M. Brian
Abstract : An ATP-dependent binding cassette transporter contributes to plant resistance to infection by Pseudomonas syringae and tolerance of abscisic acid . Abstract: Plants have been shown previously to perceive bacteria on the leaf surface and respond by closing their stomata. The virulent bacterial pathogen Pseudomonas syringae pv tomato DC3000 ( PstDC3000 ) responds by secreting a virulence factor, coronatine, which blocks the functioning of guard cells and forces stomata to reopen. After it is inside the leaf, PstDC3000 has been shown to up-regulate abscisic acid (ABA ) signaling and thereby suppress salicylic acid-dependent resistance. Some wild plants exhibit resistance to PstDC3000, but the mechanisms by which they achieve this resistance remain unknown. Here, we used genome-wide association mapping to identify an ATP-dependent binding cassette transporter gene ( ATP-dependent binding cassette transporter G family member16 ) in Arabidopsis ( Arabidopsis thaliana ) that contributes to wild plant resistance to PstDC3000 . Through microarray analysis and β-glucuronidase reporter lines, we showed that the gene is up-regulated by ABA, bacterial infection, and coronatine. We also used a green fluorescent protein fusion protein and found that transporter is more likely to localize on plasma membranes than in cell walls. Transferred DNA insertion lines exhibited consistent defective tolerance of exogenous ABA and reduced resistance to infection by PstDC3000 . Our conclusion is that ATP-dependent binding cassette transporter G family member16 is involved in ABA tolerance and contributes to plant resistance against PstDC3000 . This is one of the first examples, to our knowledge, of ATP-dependent binding cassette transporter involvement in plant resistance to infection by a bacterial pathogen. It also suggests a possible mechanism by which plants reduce the deleterious effects of ABA hijacking during pathogen attack. Collectively, these results improve our understanding of basal resistance in Arabidopsis and offer unique ABA -related targets for improving the innate resistance of plants to bacterial infection.